Payment for Non-Standard Forms of Labor and their Impact on the Economy and Social Status of Employees - YAROSHENKO, Oleg M.; LUTSENKO, Оlena Yе.; MELNYCHUK, Nataliia O.; ZHYGALKIN, Ivan P.; DEMENKO, Oleksandr Yе. (Theoretical and Practical Research in Economic Fields, 2023)
Today, in the context of the formation of a new historical phase of social development of civilization - post-industrial society - there is a de-standardization of employment, i.e. the spread of flexible and variable forms of employment, which are called non-standard. It is the modification of traditional and the emergence of completely new forms of employment that actively influence the main parameters of the labor market (demand, supply, labor price, etc.). Therefore, today, personnel leasing, outsourcing, outstaffing, remote employment, non-standard working hours, etc. can be considered fundamental innovations in the field of employment. The following methods were used during the study: analysis, synthesis, induction, deduction, dialectical approach, analytical thinking, abstraction, and generalization. The purpose of the study is to define the essence of precarious forms of labor, their impact on the economy and social protection of the employee, advantages, and disadvantages. Also, to investigate problematic theoretical and practical issues related to the right to remuneration in Ukraine in the context of precarious employment, in particular, to summarize the main directions of reforming legal regulation in this area.